Neurosteroidy a jejich význam - Bicíková, M; Hampl, R (Casopis lekaru ceskych, 2007)
Neurosteroids are steroid structure hormones with neuroactive function. Neurosteroids have rapid, non-genomic actions in CNS. Non-conjugated metabolites of progesterone such as allopregnanolone, are potent positive modulators of GABAA receptors. They open ion channels for Cl- with analgetic, hypnotic, anxiolytic and anticonvulsant effects. By sulphatation the modulation on GABAA receptors is changed to negative with opposite effect. 19-C-steroids as dehydroepiandrosterone and its sulphate are negative modulators of GABAA receptors acting as an excitant and proconvulsant. They are able to modulate positively N-methyl-D-aspartate (NMDA) receptors and open ion canals for Ca2+. Changed (lowered) neurosteroid levels can be involved in many pathological processes as premenstrual syndrome, stress, depression, some forms of epilepsy, Alzheimer disease etc. Future study targeted on regulation of their production and metabolism and understanding of the mechanism of their actions will help to use them therapeutically.
Keywords: Dehydroepiandrosterone; centrální nervový systém; receptory GABA-A; Steroids; Calcium Channels; pregnanolon; Pregnanolone; steroidy; dehydroepiandrosteron; Central Nervous System; lidé; Receptors, GABA-A; GABA modulátory; GABA Modulators; Humans; vápníkové kanály